The Campus Canopy,1941-02-01 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1941)
The Campus Canopy, February 1, 1941. Vol. 7, No. 14. -- Concert For BWR Will Be Given -- Summer Makes Canopy Staff Appointments -- Who’s Who Among The Freshman Is Announced -- Nominations For S. G. A. Offices To Be Posted -- Sule, McDowell To Be Featured In Concert Here -- Parham, Parks, Wade Are On Sunday Program -- Hill And Bottle Clash On Street -- Art In Action Seen As Classes Make Progress -- Card Exhibit Is In Upper Rotunda -- Mysterious Oracle Foretells Shadowy Future For 'Believers’
Digitized from original print, Valdosta State University Archives and Special Collections, January 25, 2017.
Keywords: The Campus Canopy; The Georgia State Woman's College; GSWC; VSC; VSU; 1940s; 1941; Valdosta State College; Valdosta State University